2017
DOI: 10.18632/oncotarget.15393
|View full text |Cite
|
Sign up to set email alerts
|

Increased reactive oxygen species levels cause ER stress and cytotoxicity in andrographolide treated colon cancer cells

Abstract: Chemotherapy continues to play an essential role in the management of many cancers including colon cancer, the third leading cause of death due to cancer in the United States. Many naturally occurring plant compounds have been demonstrated to possess anti-cancer cell activity and have the potential to supplement existing chemotherapy strategies. The plant metabolite andrographolide induces cell death in cancer cells and apoptosis is dependent upon the induction of endoplasmic reticulum stress (ER stress) leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 45 publications
2
70
0
Order By: Relevance
“…2) However, in the subsequent study we found, AGP induces ER stress leading to apoptosis through the induction of Reactive Oxygen Species (ROS) and play an important role in down-regulating cell cycle progression and cell survival pathways as well. 3) In addition, we have also demonstrated that AGP downregulates the Akt/mTOR survival pathway in this model [17]. In our study, we also observed inactivation of NF-kβ in andrographolide treated colon cancer cells (data not shown) similar to the previously reported [25].…”
Section: Exogenous Vegf Restores Akt Phosphorylation and Suppresses Rsupporting
confidence: 89%
“…2) However, in the subsequent study we found, AGP induces ER stress leading to apoptosis through the induction of Reactive Oxygen Species (ROS) and play an important role in down-regulating cell cycle progression and cell survival pathways as well. 3) In addition, we have also demonstrated that AGP downregulates the Akt/mTOR survival pathway in this model [17]. In our study, we also observed inactivation of NF-kβ in andrographolide treated colon cancer cells (data not shown) similar to the previously reported [25].…”
Section: Exogenous Vegf Restores Akt Phosphorylation and Suppresses Rsupporting
confidence: 89%
“…Intracellular abnormalities related to the function of ER, such as activation of unfolded protein response (UPR), trigger ER stress 13 . Prevalence of ER stress is also associated with the oxidative stress in cancer cells 14 . Oxidative stress causes cellular damage by ROS production in cells with compromised antioxidant resistance mechanism.…”
mentioning
confidence: 99%
“…It is known that an increase in Reactive oxygen species (ROS), including hydrogen peroxide (H 2 O 2 ), superoxide (O − 2 ) and hydroxyl radical (•OH), impairs intracellular calcium homeostasis and subsequently results in ER stress [33]. Pan et al (2010) found that H 2 O 2 increased oxidative stress and up-regulated the expressions of GRP-78 and GADD153 in rat phenocromocytoma Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…PC12 cells [34]. Banerjee et al (2017) reported that that andrographolide treatment induced ROS production in colon cancer cells and that elevated ROS caused ER stress, which subsequently inducing cell apoptosis process [33]. In order to examine whether taurine exerted cytoprotective effects against H 2 O 2 induced oxidative stress related to ER stress, Western blot analysis was employed to assay the protein levels of Collagen II and three ER stress markers.…”
Section: Discussionmentioning
confidence: 99%